Appraisal of MsepCSP14 for chemosensory functions in Mythimna separata. (6th April 2021) - Younas, Aneela; Waris, Muhammad Irfan; Shaaban, Muhammad; Tahir ul Qamar, Muhammad; Wang, Man‐Qun
Abstract: Chemosensory proteins (CSPs) have great contributions in performing diverse functions in insects. However, physiological appraisal of chemosensory protein genes still remains elusive in insects. We studied expression patterns and binding affinities of MsepCSP14, a chemosensory protein, in Mythimna separata . The distinct functions of MsepCSP14 were validated by employing different molecular techniques. The MsepCSP14 had high resemblance of sequence with chemosensory proteins of other insect family members. The MsepCSP14 expression was higher in antennal tissues of females than other tissues. Fluorescence binding assay validated that binding of nine out of 21 ligands to MsepCSP14 was higher at pH 7.4 than at pH 5.0. Three dimensional modeling (3D) and docking analysis predicted that amino acid residues of MsepCSP14 were involved in binding of compounds, and behavior assay displayed that adults of M. separata considerably responded to four volatiles from compounds demonstrating strong binding ability to MsepCSP14. Results of the present study suggest that MsepCSP14 is likely to mediate chemosensory functions in M. separata . Abstract :